Admission Hyperglycemia Predicts a Worse Outcome in Stroke Patients Treated With Intravenous Thrombolysis - Poppe, Alexandre Y. (American Diabetes Association, 2009)
OBJECTIVE: Admission hyperglycemia has been associated with worse outcomes in ischemic stroke. We hypothesized that hyperglycemia (glucose >8.0 mmol/l) in the hyperacute phase would be independently associated with increased mortality, symptomatic intracerebral hemorrhage (SICH), and poor functional status at 90 days in stroke patients treated with intravenous tissue plasminogen activator (IV-tPA). RESEARCH DESIGN AND METHODS: Using data from the prospective, multicenter Canadian Alteplase for Stroke Effectiveness Study (CASES), the association between admission glucose >8.0 mmol/l and mortality, SICH, and poor functional status at 90 days (modified Rankin Scale >1) was examined. Similar analyses examining glucose as a continuous measure were conducted. RESULTS: Of 1,098 patients, 296 (27%) had admission hyperglycemia, including 18% of those without diabetes and 70% of those with diabetes. After multivariable logistic regression, admission hyperglycemia was found to be independently associated with increased risk of death (adjusted risk ratio 1.5 [95% CI 1.2–1.9]), SICH (1.69 [0.95–3.00]), and a decreased probability of a favorable outcome at 90 days (0.7 [0.5–0.9]). An incremental risk of death and SICH and unfavorable 90-day outcomes was observed with increasing admission glucose. This observation held true for patients with and without diabetes. CONCLUSIONS: In this cohort of IV-tPA–treated stroke patients, admission hyperglycemia was independently associated with increased risk of death, SICH, and poor functional status at 90 days. Treatment trials continue to be urgently needed to determine whether this is a modifiable risk factor for poor outcome.